Sudden and Transient Block of Left Brain Hemisphere Activity in Catatonic Patients Undergoing Electroconvulsive Therapy (ECT) - Melo, António (2023)
Introduction: In the last 21 years, there has been an increase in studies on visual and quantitative EEG (qEEG). Although new findings have been reported, such as the extreme delta brush waves in anti-NMDA receptors encephalitis, there are still undocumented visual EEG alterations. In Psychiatry, these new findings are harder to detect because most patients do not undergo routine EEG. In this work, we report for the first time an EEG finding of a sudden and transient block of left brain hemisphere activity in two patients who underwent treatment with ECT. Methods: The EEG activity of the two patients undergoing ECT treatment was recorded using a Thymatron System IV device. Patient number 1: 23 year-old man with severe major depressive disorder with psychotic features and catatonia. Patient number 2: 48 year-old woman with bipolar disorder with mixed features and catatonia. Results and Discussion: The EEG recording of these two patients during their ECTs sessions showed a sudden and transient block (or arrest) of the left brain hemisphere activity. These findings are not attributed to background noise, electrode disconnection or device malfunction. Also, they were detected in two different patients. In patient 2 in two distinct admissions, two hospitals, utilizing two devices and by two different observers. After clinical improvement, these EEG alterations were not detected. Conclusion: To our knowledge, this is the first report of a sudden and transient block of the left brain hemisphere activity in psychiatric patients. Although the exact meaning of this finding remains unknown, a comparison can be made between this transient bradypsychia/block (arrest) of brain activity and bradycardia events in cardiology. We acknowledge the need for further studies to better understand these findings, particularly studies addressing different EEG abnormalities and the clinical traits they are associated with.